Differentiating Between Fluorescence-Quenching Metal Ions with Polyfluorophore Sensors Built on a DNA Backbone - Tan, Samuel S. (2011)
A common problem in detecting metal ions with fluorescent sensors is the emission-suppressing effects of fluorescence-quenching metal ions. This quenching tendency makes it difficult to design sensors with turn-on signal, and differentiate between several metal ions that may yield a strong quenching response. To address these challenges, we investigate a new sensor design strategy, incorporating fluorophores and metal ligands as DNA base replacements in DNA-like oligomers, for generating a broader range of responses for quenching metal ions. The modular molecular design enabled rapid synthesis and discovery of sensors from libraries on PEG-polystyrene beads. Using this approach, water-soluble sensors 1-5 were identified as strong responders to a set of eight typically quenching metal ions (Co(2+), Ni(2+), Cu(2+), Hg(2+), Pb(2+), Ag(+), Cr(3+), and Fe(3+)). They were synthesized and characterized for sensing responses in solution. Cross-screening with the full set of metal ions showed that they have a wide variety of responses, including emission enhancements and red- and blue-shifts. The diversity of sensor responses allows as few as two sensors (1 and 2) to be used together to successfully differentiate these eight metals. As a test, a set of unknown metal ion solutions in blind studies were also successfully identified based on the response pattern of the sensors. The modular nature of the sensor design strategy suggests a broadly applicable approach to finding sensors for differentiating many different cations by pattern-based recognition, simply by varying the sequence and composition of ligands and fluorophores on a DNA synthesizer.